2021
DOI: 10.3390/machines9120355
|View full text |Cite
|
Sign up to set email alerts
|

A Robotic Milling System Based on 3D Point Cloud

Abstract: Industrial robots have advantages in the processing of large-scale components in the aerospace industry. Compared to CNC machine tools, robot arms are cheaper and easier to deploy. However, due to the poor consistency of incoming materials, large-scale and lightweight components make it difficult to automate robotic machining. In addition, the stiffness of the tandem structure is quite low. Therefore, the stability of the milling process is always a concern. In this paper, the robotic milling research is carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Laser sensors have also been widely used in the field of grinding. Gao, Y et al carried out research on robot grinding technology for welding pretreatment technology of large parts [ 59 ], and adopted a laser profilometer for on-site measurement, planning and processing. At AUTOMATICA 2018 in Munich, Fraunhofer IPA and PILZ, a member of the Ros Industrial Consortium, presented an on-site measure–plan–process grinding robot, as shown in Figure 13 .…”
Section: Classification Of Intelligent Grinding Methodsmentioning
confidence: 99%
“…Laser sensors have also been widely used in the field of grinding. Gao, Y et al carried out research on robot grinding technology for welding pretreatment technology of large parts [ 59 ], and adopted a laser profilometer for on-site measurement, planning and processing. At AUTOMATICA 2018 in Munich, Fraunhofer IPA and PILZ, a member of the Ros Industrial Consortium, presented an on-site measure–plan–process grinding robot, as shown in Figure 13 .…”
Section: Classification Of Intelligent Grinding Methodsmentioning
confidence: 99%
“…Turntables, also known as rotary tables, positioners, or positioning tables, have emerged as indispensable tools in manufacturing, particularly within robotic manufacturing processes such as milling [1][2][3][4] and welding [5][6][7] due to their ability to improve the degree of freedom of workpieces or tools. Furthermore, turntables find extensive utility in measurement applications, including body scanners [8], industrial parts scanners [9], plant scanners [10], and various 3D reconstruction applications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In general, traditional computer numerical control (CNC) machine tools in the field of mechanical manufacturing are dedicated to high-accuracy tasks, such as milling, grinding, and drilling, while industrial robots are usually adopted for dull and dirty work scenes to replace human workers. The robots are mainly designed to perform repetitive work with relatively low accuracy, such as transferring, palletizing, and painting [1][2][3]. However, owing to their considerable advantages such as high flexibility, large workspace, and cost-efficiency, industrial robots have attracted increasing attention in the manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%